Impact of Choice of Prophylaxis on the Microbiology of Cardiac Implantable Electronic Device Infections: Insights From the Prevention of Arrhythmia Device Infection Trial (PADIT). (14th October 2021) - Longtin, Yves; Gervais, Philippe; Birnie, David H; Wang, Jia; Alings, Marco; Philippon, François; Parkash, Ratika; Manlucu, Jaimie; Angaran, Paul; Rinne, Claus; Coutu, Benoit; Low, R Aaron; et al.
Abstract: Background: The Prevention of Arrhythmia Device Infection Trial (PADIT) investigated whether intensification of perioperative prophylaxis could prevent cardiac implantable electronic device (CIED) infections. Compared with a single dose of cefazolin, the perioperative administration of cefazolin, vancomycin, bacitracin, and cephalexin did not significantly decrease the risk of infection. Our objective was to compare the microbiology of infections between study arms in PADIT. Methods: This was a post hoc analysis. Differences between study arms in the microbiology of infections were assessed at the level of individual patients and at the level of microorganisms using the Fisher exact test. Results: Overall, 209 microorganisms were reported from 177 patients. The most common microorganisms were coagulase-negative staphylococci (CoNS; 82/209 [39.2%]) and S. aureus (75/209 [35.9%]). There was a significantly lower proportion of CoNS in the incremental arm compared with the standard arm (30.1% vs 46.6%; P  = .04). However, there was no significant difference between study arms in the frequency of recovery of other microorganisms. In terms of antimicrobial susceptibility, 26.5% of microorganisms were resistant to cefazolin. CoNS were more likely to be cefazolin-resistant in the incremental arm (52.2% vs 26.8%, respectively; P  = .05). However, there was no difference between study arms in terms of infections in which the main pathogen was sensitive to cefazolin (77.8% vs 64.3%; P  = .10) or vancomycin (90.8% vs 90.2%; P  = .90). Conclusions: Intensification of the prophylaxis led to significant changes in the microbiology of infections, despite the absence of a decrease in the overall risk of infections. These findings provide important insight on the physiopathology of CIED infections. Trial registration: NCT01002911.